MANAJEMEN STRES PADA KOMUNITAS PESISIR: PERAN PERAWAT JIWA DI KOTA PARIAMAN - Dwi Happy Anggia Sari; Debby Sinthania; Mike Asmaria; Kheniva Diah Anggita (Ensiklopedia of Journal, 2025)
Coastal communities face significant stressors related to unstable income, climate variability, marine ecosystem degradation, and family burdens. This study examines stress management in coastal communities of Kota Pariaman and explores the strategic role of psychiatric nurses in preventive mental health efforts. Using community assessment, interviews, and Focus Group Discussion (FGD), 30 participants were included from three coastal subdistricts. Results reveal moderately high stress levels (62%) influenced by economic hardship and occupational demands. Psychoeducation and early detection significantly improved knowledge (t = -6.112, p 0.05). Strengthening community-based psychiatric nursing is crucial to enhancing mental resilience in coastal populations. Keywords:  Stress Management; Psychiatric Nursing; Coastal Communities; Pariaman